Potensi Karbon Biru Ekosistem Mangrove dan Pengelolaannya untuk Mendorong Mitigasi Perubahan Iklim di Indonesia - Rahman, Rahman; Lokollo, Frijona F; Wawo, Mintje; Lewerissa, Yona A; Hulopi, Mahriyana; Ceanturi, Ardan; Handayani, Luluk D; Zuhri, Muhammad Isnan; Effendi, Hefni; Wardiatno, Yusli (Universitas Gadjah Mada, 2024)
This research aimed to analyze blue carbon potential and mangrove ecosystem management in promoting climate change mitigation in Indonesia. The collected data included mangrove area data obtained through the Indonesian National Ecosystem Monitoring System (SIMONTANA). This research calculated the carbon stock using the global average of mangrove carbon stock. The results showed that the total blue carbon stored in mangrove ecosystems reached 3,267.87 Megaton Carbon (MtC). Papua and Kalimantan regions contributed the most significant potential, with 1,707.22 MtC and 608.17 MtC, respectively. The absorption of carbon dioxide (CO2) reached 11,982.21 MtCO2e. The most significant CO2 gas emissions absorption was observed in the Papua region, amounting to 6,259.80 MtCO2e, followed by Sumatra with 2,118.59 MtCO2e. This high potential value correlated with mangrove ecosystem management policies, such as conservation, restoration, and blue carbon monetization. Mangrove management for climate change mitigation was carried out through national and international cooperation to achieve the 26% to 40% emission reduction target. The existing management model of mangrove ecosystems focused on improving ecological sustainability with less orientation on improving community welfare. Implementing blue carbon monetization at the district level by involving the community as the owners or managers of the mangrove ecosystems is crucial.